Factors Affecting Fruit Quality in Strawberries Grown in a Subtropical Environment - Agüero, Juan José (2015)
Variations of strawberry fruit quality due to year, harvest date, cultivar, and nutrition were studied in Tucumán, Argentina. ‘Camarosa’, ‘Camino Real’, ‘Candonga’, and ‘Ventana’ were fertilized with “C” (control; 120 kg N/ha, 70 kg P2O5/ha, 220 kg K2O/ha, 40 kg CaO/ha, and 20 kg MgO/ha) and “1.5C” in 2006, “C”, “1.33C”, and “1.66C” in 2007, and “C”, “1.5C”, and “2C” in 2008, without affecting fruit quality. Fruit weight decreased with temperature and crop load. Firmness decreased with rainfall and temperature. Redness increased with temperature and decreased with rainfall. Soluble solids content decreased with crop load. Titratable acidity increased with temperature.